Determinants of low birth weight babies delivered at paropakar maternity and Women’s hospital: A case-control study - Sadiksha Pokhrel; Paras Kumar Pokharel; Anup Ghimire; Birendra Kumar Yadav; Avaniendra Chakravartty; Swastika Poudel; Laxmiswori Prajapati; Akshaya Acharya (PLoS ONE, 2026)
Background Low birth weight remains a major public health concern due to its association with adverse neonatal, developmental, and long-term health outcomes, with no substantial improvement observed over the past decade in Nepal. Multiple socioeconomic, maternal, and obstetric factors contribute to low birth weight, particularly in low-resource settings. This study aimed to identify the determinants of low birth weight babies delivered at Paropakar Maternity and Women’s Hospital in Kathmandu, Nepal. Methods A hospital-based age-matched (± 5 years) case-control study was carried out from 1 st August 2024–30 th January 2025 among mothers who delivered live babies at Paropakar Maternity and Women’s Hospital. A total of 57 cases (birth weight < 2500 g) and 114 controls (birth weight ≥2500 g) in the ratio of 1:2 were selected. Data on exposure variables were collected through interviews and medical records review. Chi-square test, Mann-Whitney U test and binary logistic regression were performed at 95% confidence interval (CI) to find the significant determinants of low birth weight by using SPSS version 11.5. Results Multivariate logistic regression analysis revealed that independent risk factors of LBW babies were educational status of mother (AOR: 6.32; 95% CI 1.90 to 21.05), per capita income (AOR: 2.89; 95% CI 1.02 to 8.18), parity (AOR: 4.80; 95% CI 1.91 to 12.07), hemoglobin level (AOR: 6.19; 95% CI 1.79 to 21.38), period of gestation (AOR: 8.16; 95% CI 2.42 to 27.49), weight before pregnancy (AOR: 4.86; 95% CI 1.02 to 23.29), history of chronic medical illness (AOR: 8.22; 95% CI 2.25 to 29.99) and illness during pregnancy (AOR: 3.33; 95% CI 1.20 to 9.28), type of diet (AOR: 4.84; 95% CI 1.14 to 20.64). Conclusion The findings emphasize the importance of maternal health, nutrition, and prenatal care in preventing low birth weight. Interventions targeting maternal education, nutritional status, regular antenatal care, and timely management of maternal illnesses may reduce the incidence of low birth weight.